Erythropoietin Receptor (EpoR) Agonism Is Used to Treat a Wide Range of Disease - Fabian Sanchis-Gomar; Carme Perez-Quilis; Giuseppe Lippi (BMC, 2013)
Abstract The erythropoietin receptor (EpoR) was discovered and described in red blood cells (RBCs), stimulating its proliferation and survival. The target in humans for EpoR agonists drugs appears clear-to treat anemia. However, there is evidence of the pleitropic actions of erythropoietin (Epo). For that reason, rhEpo therapy was suggested as a reliable approach for treating a broad range of pathologies, including heart and cardiovascular diseases, neurodegenerative disorders (Parkinson's and Alzheimer's disease), spinal cord injury, stroke, diabetic retinopathy and rare diseases (Friedreich ataxia). Unfortunately, the side effects of rhEpo are also evident. A new generation of nonhematopoietic EpoR agonists drugs (asialoEpo, Cepo and ARA 290) have been investigated and further developed. These EpoR agonists, without the erythropoietic activity of Epo, while preserving its tissue-protective properties, will provide better outcomes in ongoing clinical trials. Nonhematopoietic EpoR agonists represent safer and more effective surrogates for the treatment of several diseases such as brain and peripheral nerve injury, diabetic complications, renal ischemia, rare diseases, myocardial infarction, chronic heart disease and others.